Social media for intelligent public information and warning in disasters: An interdisciplinary review - Zhang, Cheng; Fan, Chao; Yao, Wenlin; Hu, Xia; Mostafavi, Ali (International journal of information management, 2019)
[Display omitted] •The vision of intelligent public information and warning is identified.•Social media contributes to three functions of public information and warning.•Studies on communication phenomena and social media informatics are reviewed.•A research roadmap is proposed to address the challenges of achieving the vision. Social media offers participatory and collaborative structure and collective knowledge building capacity to the public information and warning approaches. Therefore, the author envisions the intelligent public information and warning in disaster based on social media, which has three functions: (1) efficiently and effectively acquiring disaster situational awareness information, (2) supporting self-organized peer-to-peer help activities, and (3) enabling the disaster management agencies to hear from the public. To achieve this vision, authors of this study examined 304 studies conducted 2008 through 2018 to systemically evaluate the current literature in understanding the phenomena of communication on social media and the state-of-the-art studies on social media informatics in disasters. This review then identified the challenges of existing studies and proposed a research roadmap to address the challenges of achieving the vision. This review could serve as a bridge for researchers working on social media in disasters to understand the state-of-the-art of this problem in other related domains. The findings of this review highlight the value of certain research areas, e.g., (1) a fine-grained disaster social media ontology with semantic interoperability, (2) network pattern of trending information and emerging influential users, (3) fine-grained assessment of societal impacts due to infrastructure disruptions, and (4) best practices for social media usage during disasters.